Placental Vascular and Inflammatory Findings from Pregnancies Diagnosed with Coronavirus Disease 2019: A Systematic Review and Meta-analysis - Hessami, Kamran; Aagaard, Kjersti M.; Castro, Eumenia C.; Arian, Sara E.; Nassr, Ahmed A.; Barrozo, Enrico R.; Seferovic, Maxim D.; Shamshirsaz, Alireza A. (American Journal of Perinatology, 2022)
We aimed to perform a meta-analysis of the literature concerning histopathologic findings in the placentas of women with SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) infection during pregnancy. Searches for articles in English included PubMed, Web of Science, Google Scholar, and reference lists (up to April 2021). Studies presenting data on placental histopathology according to the Amsterdam Consensus Group criteria in SARS-CoV-2 positive and negative pregnancies were identified. Lesions were categorized into: maternal and fetal vascular malperfusion (MVM and FVM, respectively), acute placental inflammation with maternal and fetal inflammatory response (MIR and FIR, respectively), chronic inflammatory lesions (CILs), and increased perivillous fibrin deposition (PVFD). A total of 15 studies reporting on 19,025 placentas, n = 699 of which were derived from women who were identified as being infected with SARS-CoV-2 and 18,326 as SARS-CoV-2-negative controls, were eligible for analysis. No significant difference in incidence of MVM (odds ratio [OR]: 1.18, 95% confidence interval [CI]: 0.73–1.90), FVM (OR: 1.23, 95% CI: 0.63–2.42), MIR (OR: 0.66, 95% CI: 0.29–1.52) or FIR (OR: 0.85, 95% CI: 0.44–1.63), and CILs (OR: 0.97, 95% CI: 0.55–1.72) was found between placentae from gravida identified as being SARS-CoV-2 infected. However, placenta from gravida identified as being infected with SARS-CoV-2 were associated with significantly increased occurrence of PVFD (OR: 2.77, 95% CI: 1.06–7.27). After subgroup analyses based on clinical severity of COVID-19 infection, no significant difference was observed in terms of reported placental pathology between symptomatic or asymptomatic SARS-CoV-2 gravidae placenta. Current evidence based on the available literature suggests that the only pathologic finding in the placentae of women who are pregnant identified as having been infected with SARS-CoV-2 was an increased prevalence of PVFD.Key Points
Keywords: COVID-19; SARS-CoV-2; placenta; pregnancy; pathology; meta-analysis